2019
DOI: 10.1080/21691401.2019.1614016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Srxn1 on growth and Notch signalling of astrocyte induced by hydrogen peroxide

Abstract: Objective: To investigate the effect of Sulfiredoxin-1 (Srxn1) on astrocyte injury induced by hydrogen peroxide (H 2 O 2 ). Methods: Observing the changes of H 2 O 2 on contents of lactate dehydrogenase (LDH), malondialdehyde (MDA), superoxide dismutase (SOD) and apoptosis after transfected Srxn1 siRNA into astrocytes. The protein expression of Notch 1, NICD and Hes1, the content of LDH and MDA, the activity of SOD and apoptosis rate of astrocytes after inhibiting or activation of Notch signalling pathway were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…32) According to reports, the expression level of Srxn1 was increased when cells were stimulated by external injury. 33,34) In this study, we used PDGF-BB to treat MOVAS cells and found that treatment of PDGF-BB increased the mRNA and protein expression of Srxn1 in a dose-and time-dependent manner, which was consistent with previous studies. PDGF interacts with PDGF receptor (PDGFR) on cell membrane inducing dimerization and the phosphorylation of PDGFR can activate several downstream signaling pathways such as Ras/Rac, MAPK, PI3 K, STAT, and Src, which is essential for the regulation of cellular function.…”
Section: Discussionsupporting
confidence: 89%
“…32) According to reports, the expression level of Srxn1 was increased when cells were stimulated by external injury. 33,34) In this study, we used PDGF-BB to treat MOVAS cells and found that treatment of PDGF-BB increased the mRNA and protein expression of Srxn1 in a dose-and time-dependent manner, which was consistent with previous studies. PDGF interacts with PDGF receptor (PDGFR) on cell membrane inducing dimerization and the phosphorylation of PDGFR can activate several downstream signaling pathways such as Ras/Rac, MAPK, PI3 K, STAT, and Src, which is essential for the regulation of cellular function.…”
Section: Discussionsupporting
confidence: 89%
“…SRXN1 , an endogenous antioxidant, has been shown to protect against exogenous compound-induced oxidative stress in vitro and in vivo ( 42 , 43 ). However, numerous studies reported that the anti-oxidative stress effect of SRXN1 could not protect against pulmonary disease ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…POD activity was measured using the protocols described by Sharma et al [47]. SOD activity was measured following the methods used previously [48]. CAT activity was measured following Han et al [49].…”
Section: Determination Of Related Physiological Indexesmentioning
confidence: 99%